Persepsi Masyarakat Terhadap Sport Massage Pada Desa Sepulu Kecamatan Sepulu Kabupaten Bangkalan - Ali Akbar; Joesoef Roepajadi (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the perception of the Sepulu Village community towards sport massage. This research uses a descriptive type with a quantitative approach. The data collection method uses a survey method with an instrument in the form of a questionnaire which is given manually to respondents with 21 statement items to determine the public's perception of sport massage. The population in this study were people in Sepulu Village who usually do traditional massage, aged 18-40 years and people with heavy physical bodies, totaling 5,367 people. Using sampling technique purposive sampling totaling 98 people. The data analysis technique uses quantitative descriptive data analysis with percentages. The results of this research indicate that public perception of sport massage in Sepulu Village, Sepulu District, Bangkalan Regency, there were 40 respondents (40,82%) in the very good category, 35 respondents (35,71%) in the good category, 17 respondents (17,35%) in the not good category, 6 respondents (6,12%) in the very bad category. So, the conclusion is that the percentage of people's perception of the highest sport massage in Sepulu Village, Sepulu District, Bangkalan Regency is 40,82% in the very good category.